Significantly higher atherosclerosis risks in patients with obstructive sleep apnea and non-alcoholic fatty liver disease. - Samshol Sukahri (Public Library of Science (PLoS), 2021)
Introduction There is limited data on the relationship between Obstructive Sleep Apnea (OSA) and Non-Alcoholic Fatty Liver Disease (NAFLD), each associated with increased cardiovascular risk. This study aimed to determine the relationships between severity of OSA, degree of steatosis in NAFLD and cardiovascular risk via CIMT and atherosclerosis markers ie intracellular adhesion molecule-1 (ICAM-1) an Lipoprotein-a (Lp(a)) in a group of patients with OSA. Materials and methods This was a cross-sectional, single center study. A total of 110 subjects between 18 to 65 years of age and diagnosed with OSA following sleep study examinations were recruited. Exclusion criteria included seropositive Hepatitis B or Hepatitis C, and significant alcohol intake. Result The prevalence of NAFLD was 81.8%. The mean CIMT (0.08±0.03 vs 0.06±0.01 cm, p = 0.001), ICAM-1 (334.53±72.86 vs 265.46±102.92 ng/mL, p = 0.001) and Lp(a) (85.41±52.56 vs 23.55±23.66 nmol/L, p<0.001) were significantly higher in the NAFLD group compared to the non-NAFLD group. Comparisons between the different groups showed significantly increasing levels of CIMT, ICAM-1 and Lp(a), lowest within the non-NAFLD, followed by the NAFLD 1 and NAFLD 2+3 groups. There was a significant positive correlation between degree of steatosis and the severity of OSA (r = 0.453, p<0.001). Logistic regression analysis revealed that patients with apnea/hypopnea index (AHI) of >30 were 52.77 (CI 6.34, 439.14) times more likely to have NAFLD compared to those with mild AHI (p<0.001). Conclusion The prevalence of NAFLD is alarmingly high in this group of OSA patients. The degree of steatosis in patients with NAFLD was significantly correlated with severity of OSA, CIMT measurements, ICAM-1 and Lp(a). Our findings underscore screening for NAFLD in patients with OSA to ensure prompt risk stratification and management.